How Coopetition Influences Environmental Performance: Role of Financial Slack, Leverage, and Leanness - Modi, Sachin B.; Cantor, David E. (Production and Operations Management, 2021)
Focal firms are struggling to improve their environmental performance for several reasons, including a scarcity of internal and external environmental resources. This study suggests that coopetition provides a boost to a focal firm’s environmental performance. In particular, this research theorizes that a coopetitor firm’s environmental performance has a spillover effect on a focal firm’s environmental performance. This study also investigates the moderating role of a focal firm’s financial slack, financial leverage, and inventory leanness on this relationship. The empirical analysis indicates that coopetitor firms’ environmental performance significantly influences a focal firm’s environmental performance. This relationship is weaker for firms with higher financial slack, and stronger for firms that have lower financial leverage and higher leanness. Collectively, these findings provide important managerial and research implications regarding the consequences of coopetition on a focal firm’s environmental performance.